Acrylamide Optical Sensor Based on Hydrolysis Using Bacillus sp Strain ZK34 Containing Amidase Properties - Chong Y.-M.; Ahmad M.; Heng L.Y.; Kusnin N.; Shukor M.Y.A. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by SCOPUS